TONY PALMER – AN HONORARY PROFESSOR OF LESYA UKRAINKA EASTERN EUROPEAN NATIONAL UNIVERSITY - Biskub, Iryna (Актуальні питання іноземної філології, 2021)
TONY PALMER – AN HONORARY PROFESSOR OF LESYA UKRAINKA EASTERN EUROPEAN NATIONAL UNIVERSITY